Study of placental changes in pregnancy induced hypertension - Ahmed, Maimoona; Daver, Rekha G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Study of histopathological changes in placenta in pregnancy induced hypertension (PIH). Methods: Post delivery placentas of 130 cases were examined and findings correlated with severity of PIH. Results: The mean placental weight was 438.9 gms, 374 gms and 333.86 gms and the mean fetal weight to placental weight ratio was 6.003:1, 5.6:1 and 5.27:1 in cases of mild, moderate and severe PIH respectively. Infarction was seen in 10.25%, 33.3% and 59% and calcification was present in 15.38%, 30% and 50% of the cases of mild, moderate and severe PIH respectively. Retroplacental clot was seen in 36.4% of severe PIH cases. The mean numbers of syncytial knots were 20.4 (mild PIH), 35.97 (moderate PIH) and 59.77 (severe PIH) and 77.27% of severe cases of PIH had >40% areas showing trophoblastic hyperplasia. Conclusion: PIH adversely influences the placental morphology and histopathological examination post deliveryhelps investigate the mechanism of placental dysfunction in detail.